Nutrition and Health Outcomes: Targets for Agricultural Research. Brief 43 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2014)
This brief outlines the context and the existing evidence base, together with priority research areas and key issues identified by participants at the 2013 Science Forum as those which CGIAR needs to consider in designing agricultural research that can deliver better nutrition and health outcomes.